Крупный город: автоматизация управления развитием / В. И. Мягков - Мягков Вадим Иванович (Экономика, 1990)
Экземпляры: КХ (20100819) / Инвентарный номер: 966366 / Цена: 1.40 / Сис.шифр: 65.050.9(2) / Авт.знак: М 99 / ГРНТИ: 82 / ББК: 65.050.23